2014
DOI: 10.1590/2317-1545v36n41006
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with fungicides and insecticides on the physiological quality and health of wheat seeds

Abstract: -Seed treatment with insecticides and fungicides has become an important practice for ensuring initial plant stand in establishing crops. In this context, the aim of this study was to evaluate the influence of chemical seed treatment with insecticides and fungicides on the physiological quality and health of the seeds of wheat cultivars. Seeds of the wheat cultivars BRS Pardela and BRS Gaivota were used, subjected to the following chemical treatments: 1-control, 2-carboxin + thiram + imidacloprid + thiodicarb,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 14 publications
1
15
0
3
Order By: Relevance
“…In this regard, the quality of treated seeds has been evaluated for different crops, with positive or no responses obtained for different seed treatments. The association of fungicide carboxin + thiram with insecticide imidacloprid + thiodicarb reduced germination in wheat seeds cultivar BRS Gaivota (Abati et al, 2014). In maize, the treatment with insecticide thiamethoxam, at a dose of 1.4 g. kg -1 of seeds, did not affected germination after 30 days of storage under non-control environmental conditions; however, seed vigor evaluated by cold test, reduced significantly in comparison to untreated seeds (Bittencourt et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the quality of treated seeds has been evaluated for different crops, with positive or no responses obtained for different seed treatments. The association of fungicide carboxin + thiram with insecticide imidacloprid + thiodicarb reduced germination in wheat seeds cultivar BRS Gaivota (Abati et al, 2014). In maize, the treatment with insecticide thiamethoxam, at a dose of 1.4 g. kg -1 of seeds, did not affected germination after 30 days of storage under non-control environmental conditions; however, seed vigor evaluated by cold test, reduced significantly in comparison to untreated seeds (Bittencourt et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Seed treatment showed an effect on germination only at 150 days of storage, when the industrial and conventional treatments significantly reduced the percentage of normal seedlings. Some authors suggest that the use of fungicides and insecticides in seed treatment may cause phytotoxicity, as reported by Vanin et al (2011) in sorghum, Abati et al (2014) in wheat and Brzezinski et al (2015) in soybean. In this sense, Dan et al (2010) also observed a reduced germination of soybean seeds treated with different insecticides and stored for 45 days under controlled conditions (± 27 ºC and 70 % RH), and the performance of seeds treated with thiamethoxam did not differ from those without treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The use of seeds with high physiological quality, along with the efficiency of fungicides and insecticides, is essential for high crop yields (Dan et al 2010, Abati et al 2014. The treatment of wheat 1.…”
Section: Introductionmentioning
confidence: 99%
“…Tal fato pode ser relacionado à diminuição da área superficial da massa de sementes ocasionado pelo aumento de tamanho destas, assim ocorrendo maior deposição de ingrediente ativo por unidade de área. Abati et al(2014) relatam a ocorrência de fitotoxidez em plântulas geradas a partir de sementes tratadas, ocasionando a diminuição da qualidade fisiológica destas. Assim com a diminuição relativa da área da massa de sementes e com o aumento da concentração de ingrediente ativo sobre as sementes, tal efeito pode ser mais evidente, ocasionando diminuição no vigor do lote.…”
Section: Methodsunclassified